Operative investigation in tuberculosis, role of the faculty of medicine: Investigación operativa en tuberculosis, función de la facultad de medicina - Salas Lopez, Antonio (2018)
Operational Research (IO) in Health has as its final objective to provide useful information for decision making that serve to improve Health Policies, at any level of government. The questions in the IO arise from problems detected in the field when implementing projects in Health, and the answers to these questions are intended to solve these difficulties. We propose that one of the barriers to achieving the objectives of development in Health in our environment is the weakness of our System, so the IO is presented as a useful tool to try the solutions that arise. An IO project arises, according to the Technical Document of the National Institute of Health (INS) 1, if there are three elements: a discrepancy between what is and what should be; a question about the causes of this discrepancy; and at least two plausible responses to this discrepancy. The infectious diseases are a prevalent group of pathologies in our environment, causing great morbidity and mortality. Tuberculosis (TB) is a public health problem in our country, being, Peru, considered one of the countries with the highest burden of disease in Latin America, second only to Haiti; and representing, together with Brazil, more than half of the cases in South America2. The Faculties of Medicine, with the support of their respective Research Institutes, should promote the development of Operational Research from undergraduate to postgraduate in our environment or our health institutions independent of the level of complexity, which will allow us to know certain characteristics of our reality and of our population in particular. DOI: 10.25176/RFMH.v18.n3.1586